2019
DOI: 10.3390/md17020090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oven-Drying on the Recovery of Valuable Compounds from Ulva rigida, Gracilaria sp. and Fucus vesiculosus

Abstract: The effect of oven-drying at 25, 40 and 60 °C was evaluated on three macroalgae of relevance in Europe, namely Ulva rigida, Gracilaria sp. and Fucus vesiculosus, with respect to quality aspects, including their potential to be exploited as a source of valuable compounds. Notably, as compared to freeze-drying, oven-drying at 25 °C promoted the extraction of chlorophylls and carotenoids from U. rigida, as well as those of phycoerythrin and chlorophyll a from Gracilaria sp., while 40 °C favored the recovery of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 47 publications
6
53
1
Order By: Relevance
“…Moreover, as expected, the total color difference parameter (calculated on the basis of a*, b*, and L* coordinates) confirmed that changes in colors during the storage time were particularly evident in salt-treated samples, probably due to superior changes in the cells’ structures, which might contribute to additional losses/changes in pigments. In fact, this is partially supported by the results of Figure 1, which show higher levels of extracted chlorophylls and total carotenoids (presumably lutein as shown in our previous work [15]) in air-dried U. rigida at t180, when compared to salt-treated samples.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, as expected, the total color difference parameter (calculated on the basis of a*, b*, and L* coordinates) confirmed that changes in colors during the storage time were particularly evident in salt-treated samples, probably due to superior changes in the cells’ structures, which might contribute to additional losses/changes in pigments. In fact, this is partially supported by the results of Figure 1, which show higher levels of extracted chlorophylls and total carotenoids (presumably lutein as shown in our previous work [15]) in air-dried U. rigida at t180, when compared to salt-treated samples.…”
Section: Resultssupporting
confidence: 83%
“…from Chile, together with changes in the levels of phytochemicals and the profile of amino acids and fatty acids. Moreover, our group has recently evidenced the effect of distinct oven-drying temperatures (25, 40 and 60 °C) on quality parameters and recovery yield of valuable compounds (pigments, phenolic compounds, and polysaccharides) from U. rigida , as compared to freeze-drying [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, phenolic compounds (capable of acting as antioxidants) are often depleted when using certain drying methods, which may then result in reduced antioxidant activity (Ling et al 2015;Cruces et al 2016). Other valuable biomolecules such as amino acids, proteins, lipids, fatty acids and other bioactive compounds in seaweeds can also be affected by drying procedures (Chan et al 1997;Le Lann et al 2008;Ling et al 2015;Cruces et al 2016;Neoh et al 2016;Hamid et al 2018;Sappati and Nayak 2018;Silva et al 2019). These studies have demonstrated the value of selecting appropriate drying treatments in order to preserve important bioactive compounds within seaweeds that are destined for use as functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study showed that, apart from iodine, other chemical components did not change under the influence of drying. In a recent study Silva et al [23] compared the chemical composition of Ulva rigida, Gracilaria sp. and F.vesiculosus seaweed tallomes dried in an oven (25, 40 and 60 ∘ C) compared to fresh seaweed, and showed that the extraction of polyphenols and their activity are significantly influenced by the drying method.…”
Section: Discussionmentioning
confidence: 99%